2016
DOI: 10.4103/0970-2113.173066
|View full text |Cite
|
Sign up to set email alerts
|

Transbronchial lung biopsy with a flexible cryoprobe: First case report from India

Abstract: Sarcoidosis and tuberculosis are granulomatous disorders that mimic each other both clinically and radiologically. Both can present with fever and pulmonary nodules and often require the performance of transbronchial lung biopsy (TBLB) for diagnosis. In recent studies, the flexible cryoprobe for carrying out TBLB has been found to be useful in the diagnosis of disorders diffusely involving the lung parenchyma. Here, we present the case of a 29-year-old man who presented with fever and cough and was found to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Subsequently, the second bronchoscope was inserted immediately and “wedged” into the biopsied segment to control the bleeding. In the case that we had reported,[ 4 ] we did not encounter any complication. However, in the second patient using the aforementioned technique was employed, significant bleeding was encountered that hindered the introduction of the second bronchoscope into the airway, with resultant spillage of the blood to the contralateral bronchial tree.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Subsequently, the second bronchoscope was inserted immediately and “wedged” into the biopsied segment to control the bleeding. In the case that we had reported,[ 4 ] we did not encounter any complication. However, in the second patient using the aforementioned technique was employed, significant bleeding was encountered that hindered the introduction of the second bronchoscope into the airway, with resultant spillage of the blood to the contralateral bronchial tree.…”
mentioning
confidence: 68%
“…We recently reported the first experience from India of performing cryobiopsy from the lung parenchyma (cryo-TBLB). [ 4 ] Therein, we had described a flexible bronchoscopic technique with the procedure performed under conscious sedation in a spontaneously breathing patient using two bronchoscopes. The first bronchoscope was used to obtain the cryobiopsy and was withdrawn with the lung specimen adhered to the cryoprobe.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] Exclusive use of a flexible bronchoscope may allow the performance of this procedure, but without the use of an occlusion balloon, this may be associated with unpredictable severe bleeding. [ 3 4 ] Some authors have reported the use of single flexible bronchoscope while others have used two flexible bronchoscopes in sequential manner or rendezvous method. [ 4 ] Artificial airway management options during the procedure include supraglottic airway, endotracheal tube, or rigid bronchoscope.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 4 ] Some authors have reported the use of single flexible bronchoscope while others have used two flexible bronchoscopes in sequential manner or rendezvous method. [ 4 ] Artificial airway management options during the procedure include supraglottic airway, endotracheal tube, or rigid bronchoscope. The use of rigid bronchoscope and a bronchial blocker during the procedure may be preferable to provide airway protection in case of unpredictable bleeding.…”
Section: Introductionmentioning
confidence: 99%